Architecture in the space of flows - Ballantyne, Andrew; Smith, Chris (Chris L.) (Abingdon, Oxon, [England] : Routledge, 2012)
Traditionally, architecture has been preoccupied with the resolution of form. That concern helps to make photogenic buildings, which have received a great deal of attention. This book looks instead at the idea of the flows, which connects things together and moves between things. It is more difficult to discuss, but more necessary, because it is what makes things work. Architects have to think about flow - the flow of people through buildings, the flow of energy into buildings, and waste out of them - but usually the effects of flow do not find expression. The essays gathered here present a collection of exploratory ideas and offer an understanding of buildings, people and settlements through concepts of flow. -- Book Description.
Fluxion / Andrew Ballantyne and Chris L. Smith -- Places in flux. Theoretical, conceptual, ethical, and methodological stakes to induce a new age : M.U.D. / Marc Godts and Nel Janssens -- Oceanic spaces of flow / Amanda Yates -- Interpretive flow : a 1930s trans-cultural architectural nexus / {uA073}a Andersson -- Solar flow : the uses of light in Gold Coast living / Patricia Wise -- Trade flow : architectures of informal markets / Peter Mtenbk and Helge Mooshammer -- Local flows : Rom-Hoob's phenomena of transition / Soranart Sinuraibhan -- Spaces of flow. Controlling flow : on the logistics of distributive space / Craig Martin -- Temporal flows / Steve Basson -- Navigating flow : architecture of the blogospere / Wael Salah Fahmi -- The (not so) smooth flow between architecture and life / Stephen Loo -- Envoi -- Limits of fluxion / Michael Tawa.
Includes bibliographical references and index.
Keywords: Architecture -- Philosophy; Architecture and society